Outsourcing versus in-house maintenance of medical devices: A longitudinal, empirical study (2014)
Objective. To determine what factors have a significant influence on the performance of medical device maintenance outsourcing, and to determine how the performance of external governance structures differs depending on whether a hospital is private or public. Methods. This was a longitudinal study of 590 maintenance transactions at 20 hospitals in Bogotá, Colombia, involving 764 medical devices and 72 maintenance service providers. Maintenance performance data (i.e., turn-around time in hours; TAT) for the service providers (either in-house or outsourced) were primarily collected over a 20-month period, from December 2009-August 2011, by means of a monitoring procedure; then, a hazards model was run. Results. The availability of specific repair parts, in-stock, in the city in which the medical devices were located, had a positive impact on the performance of both internal and external governance structures. Online service also had a positive impact on both, with a stronger positive impact on the performance of internal governance than on that of external governance. For transactions governed by external structures, better performance was seen in private hospitals than in public ones. In public health institutions, internal governance showed better performance than external governance. Both internal and external governance structures showed better performance in private healthcare institutions than in public ones. Conclusions. In public health institutions, internal governance shows better performance than external governance; this suggests that healthcare managers should reconsider the trend to eliminate in-house maintenance service staff in public healthcare institutions.